Design and Fabrication of Highly Reflective DBRs for use with Long Wavelength VCSELs - Shahideh, Mehdi (My University, 2004)
This project successfully designed, fabricated and characterized two highly reflective distributed Bragg reflectors for use with long wavelength vertical cavity surface emitting lasers. The first reflector consisted of 20 pairs of alternating lnP/Ino.64Gao.36Aso.777Po.223 layers grown on an InP substrate with a theoretically predicted normal incident reflectivity of 96.6% at a center wavelength of 1550nm. The second DBR had 20 pairs of alternating GaAs/Ino.484Gao.5i6P layers grown on a GaAs substrate with a theoretically predicted reflectivity of 94.9% at a center wavelength of 1550nm for normal incident light. Experimental results obtained using a specially designed reflectivity measurement setup confirmed reflectivity models and predictions at both normal and variable incident light angles. However, these measurements revealed a discrepancy between theoretical and experimental layer thickness values for both DBR structures. Applying perturbations to the theoretical models, the actual layer thicknesses of the DBRs were determined. X-ray analysis was employed to examine the periodicity of the super-lattices along with the accuracy of lattice matching to the substrate. Transmission electron microscopy revealed that no detectable drift in layer thickness was apparent during growth of the DBR structures. Photoluminescence was used to investigate any compositional variations of the quaternary layers in the first DBR stack.
Keywords: highly reflective distributed Bragg reflectors; long wavelength vertical cavity surface emitting lasers